“Talking” containers. Visual heterotopias in the picture¬books illustrated by Svein Nyhus - Dymel-Trzebiatowska, Hanna (Folia Scandinavica Posnaniensia, 2019)
The article discusses picturebooks illustrated by a Norwegian artist, Svein Nyhus, to show his specific symbolic manner of depicting the child’s environment. It is argued that the illustrator employs characteristic recurrent elements of home representations and elaborates an interesting interplay of outer and inner spaces, consistently focusing the child’s perspective. This is demonstrated by an analysis of four picturebooks by the Norwegian artist: Pappa! (1998, Daddy!), Snill (2002, Nice), Sinna mann (2003, Angry Man) and Håret till mamma (2007, Mum’s Hair). The books have been regarded as ambitious literature for children, addressing difficult issues or even sometimes breaking a taboo. To show Nyhus’ visual method of thematising childhood’s traumas in relation to a home space is also one of the aims of the paper. The analysis of visual content is carried out with references to the textual narratives, drawing on ideas about heterotopia by Michel Foucault (1984), self-effacement by Karen Horney (1997) and the poetics of space by Gaston Bachelard (1969).